The effect of personality diversity on life satisfaction and job performance: The mediate effect of mastery approach goal orientation - Park, ChiHun; Park, YoungSeok (Korean Journal of Industrial and Organizational Psychology, 2021)
The purpose of this study is to verify the effect of personality diversity on well-being in life and job performance. Personality diversity is a hypothetical construct for this study based on self-concept differentiation across roles, considering both the variability between roles and the variability within a role in personality. Personality diversity is the variety of subject-specific personality, which refers to a variety of distinctive personality that are expressed according to the role. To this end, it is examined how personality diversity relates to life satisfaction and job performance. After that, the process is explained through a mediated model by achievement goals. As a result, personality diversity showed negative relationship with life satisfaction. This result reconfirmed the previous studies. However, personality diversity had positive correlations with task performance, context performance, and adaptational performance. And even after controlling the level of personality, personality diversity showed significant incremental validity for task performance. In addition, the mastery approach goal orientation showed partial mediation effect between the personality diversity and task performance and full mediation effect between the personality diversity and the other criterion variables, contextual and adaptational performance. These results suggest that personality diversity is distinguished from the level of personality and can have adaptive effect on job performance rather than supporting the self-fragmentation hypothesis of prior researches. Finally, the need of reliability test for personality diversity and further research was suggested.